Synthesis of nitrogen and phosphorus co-doped graphene quantum dots as metal-free electrocatalysts for ethanol electrooxidation. Issue 8 (3rd August 2022) - Chalani, Mina; Daneshvari-Esfahlan, Vahid; Hosseini, Mir Ghasem
Abstract: In this study, three electrocatalysts containing graphene quantum dots, nitrogen-doped graphene quantum dots, and nitrogen and phosphorus co-doped graphene quantum dots are successfully synthesized by a simple hydrothermal method. The as-prepared electrocatalysts are characterized using spectroscopic and electrochemical techniques. The results confirm a uniform distribution and a high order structure with a nanoparticle size of 1–3 nm for all electrocatalysts. Electrochemical analysis demonstrates that the as-synthesized nitrogen and phosphorus co-doped graphene quantum dots (16.67 A g −1 ) exhibit improved catalytic activity towards ethanol oxidation reaction in alkaline media as compared to nitrogen-doped graphene quantum dots (6.903 A g −1 ) and graphene quantum dots (0.139 A g −1 ). Moreover, the nitrogen and phosphorus co-doped graphene quantum dots display a low overpotential than two other synthesized catalysts. The enhanced electrochemical performance may be related to the synergetic effect of phosphorous addition on the nitrogen-doped graphene quantum dots. Based on the results, as-prepared phosphorus and nitrogen co-doped graphene quantum dots could be a promising anodic catalyst for the direct ethanol fuel cells application.